2016
DOI: 10.21660/2016.26.5253
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Potential Assessment Based on Laboratory Test

Abstract: ABSTRACT:The physical properties of sand soil which give effect to the resistance of liquefaction include grain size and density. Those physical properties of sand soil associated to liquefaction resistance have been studied in laboratory. Based on that study, the method to assess the liquefaction potential then is proposed. In laboratory tests, the vibration source is given by using the shaking table. During the tests, the acceleration and settlement are recorded. It then concluded that there is a relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…3 shows the proposed ranges of grain size distribution for potentially liquefiable soil and most liquefiable soil [11]. This chart has been used widely such as [9], [13], [15] and [16] to indicate liquefaction potential. However, this chart limited to clean sand which containing a little or no fine contents.…”
Section: Factors Influencing Liquefaction Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…3 shows the proposed ranges of grain size distribution for potentially liquefiable soil and most liquefiable soil [11]. This chart has been used widely such as [9], [13], [15] and [16] to indicate liquefaction potential. However, this chart limited to clean sand which containing a little or no fine contents.…”
Section: Factors Influencing Liquefaction Resistancementioning
confidence: 99%
“…On the other hand, some researchers show the D50 of 0.08 mm are more susceptible to liquefy. Evaluation on field case histories of liquefaction potential for 50 years around the world have been figured out by [13] based on research done by [16]. From Fig.…”
Section: Microstructure Of Clay and Sand-fine Mixturesmentioning
confidence: 99%
“…In this study, both specimens were tested by using a horizontal uniaxial movement type of shaking table in Soil Mechanic Laboratory of Andalas University [11]. The input motions with varying the frequency of earthquake, such as the Medium earthquake (ME), Strong earthquake (SE), and Very Strong Earthquake (VSE) ( The specimens were tested in three stages.…”
Section: Test Proceduresmentioning
confidence: 99%
“…From the research results, some researchers claim that mean grain size (D 50 ) of 1.0 mm to 0.1 mm causes decreasing in liquefaction resistance, while some researchers show that the D 50 = 0.08 mm is more susceptible to liquefaction. Based on the research done by previous researcher, evaluation on field case histories of liquefaction potential for 50 years around the world have been figured out by [18]. From Figure 1, [18] concluded that about 78 % liquefaction out of 155 incidents occur when the mean grain size, D 50 is lied between 0.113 mm to 0.338 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the research done by previous researcher, evaluation on field case histories of liquefaction potential for 50 years around the world have been figured out by [18]. From Figure 1, [18] concluded that about 78 % liquefaction out of 155 incidents occur when the mean grain size, D 50 is lied between 0.113 mm to 0.338 mm. [17] show that there is no relationship can be concluded between the coefficient of uniformity, C U and coefficient of curvature, C C with the cyclic resistance.…”
Section: Introductionmentioning
confidence: 99%